Cohorting for preventing the nosocomial spread of carbapenemase-producing Enterobacterales in non-epidemic settings: should it be mandatory?. Issue 3 (July 2020) - Hilliquin, D.; Lomont, A.; Zahar, J-R.
Summary: Worldwide dissemination of carbapenemase-producing Enterobacterales (CPE) has led to national and international guidance recommending the implementation of cohorting in healthcare settings. However, in view of recent data regarding the spread of extended-spectrum β-lactamase-producing Enterobacterales, the usefulness of this measure in non-outbreak settings is questionable; here, individual contact isolation may be sufficient to control the risk of dissemination. A narrative review of the literature was conducted and the role of cohorting discussed. CPE are responsible for outbreaks in healthcare settings, which are considered the epicentre of spread of resistance strains. CPE are responsible for adverse effects such as increases in hospital stay and costs, fewer therapeutic options and thus higher risk of clinical failures and mortality. Environment and materials have also been reported as contaminated with CPE and may be the source of outbreak. Even if guidelines and publications have supported implementation of cohorting, there are no randomized studies to demonstrate that this measure should be mandatory. Most studies are descriptive and cohorting is usually one of several other measures to control outbreaks. Cohorting is not adapted to all healthcare settings, requiring human and material resources. Other measures must be strengthened such as compliance with hand hygiene, antibiotic stewardship, and surveillance of contact patients. Individual risk factors for acquisition should also be evaluated. In conclusion, local epidemiology and resources must be assessed before implementing cohorting.